Spirobifluorene‐based Porous Organic Polymers as Efficient Porous Supports for Pd and Pt for Selective Hydrogenation. Issue 1 (28th September 2018) - Trandafir, Mihaela Mirela; Pop, Lidia; Hӑdade, Niculina D.; Hristea, Ioana; Teodorescu, Cristian Mihail; Krumeich, Frank; van Bokhoven, Jeroen A.; Grosu, Ion; Parvulescu, Vasile I.
Abstract: Spirobifluorene‐based porous organic polymers (POP) were synthesized following two different protocols; the acetylenic coupling reaction conditions and the Sonogashira cross‐coupling reaction. These were utilized as support for the hydrogenation of a series of species containing unsaturated C=C and C=O bonds (4‐nitrostyrene, 4‐bromobenzophenone, acetophenone, 7‐nitro‐1‐tetralone and 1, 2‐naphtoquinone confirmed their efficiency). POP1 prepared via a copper‐catalysis protocol was completely inactive, while POP2‐4 containing residual Pd exhibited different activities in accordance to the accessibility of the substrates to the metal. Further deposition of 0.5 wt% Pd led to active and stable catalysts. They were easily separated by filtration, and after re‐dispersion, afforded the same performances for ten successive cycles. This study also evidenced the specific role of the support in these reactions by comparing the behavior of Pd/POP with that of a Pd/C catalyst with the same loading of palladium. The deposition of Pt on these supports led to sub‐nanometric particles and, in accordance, to a different catalytic behavior reflected merely by differences in the selectivity. Abstract : Once you POP you just can′t stop ! Spirobifluorene‐based porous organic polymers (POPs) were synthesized and used as supports for Pd and Pt (0.5 wt% loading). The new materials were characterized using various techniques: XRD, TEM, XPS, etc. They show a high activity and selectivity for the hydrogenation of different aromatic compounds containing unsaturated C=C and C=O bonds (4‐nitrostyrene, 4‐bromobenzophenone, acetophenone and 7‐nitro‐1‐tetralone), and a high stability and very good recoverability